2011
DOI: 10.1111/j.1471-4159.2011.07580.x
|View full text |Cite
|
Sign up to set email alerts
|

The Discoidin domain receptor 1 gene has a functional A2RE sequence

Abstract: J. Neurochem. (2012) 120, 408–418. Abstract Discoidin domain receptor 1 (DDR1) is expressed in myelin oligodendrocytes and co‐localizes with myelin basic protein (MBP). Alternative splicing of DDR1 generates five isoforms designated DDR1a–e. The MBP mRNA contains an hnRNP A2 response element (A2RE) sequence that is recognized by heterogeneous nuclear ribonucleoprotein (hnRNP) A2/B1, which is responsible for transport of the MBP mRNA to oligodendrocyte processes. We hypothesized that DDR1 could have a functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Likewise, the DNA repair protein XRCC3, which is induced by genotoxic stress, can up-regulate DDR1 expression (Martinez-Marignac et al, 2011). The DDR1 gene also contains a hnRNP A2 response element sequence, which may be involved in alternative splicing and nuclear export of DDR1 mRNA in oligodendrocytes (Roig et al, 2012). DDR1 expression is downregulated during induction of epithelial-mesenchymal transition (EMT).…”
Section: Ddr Structure and Ligand Interactionsmentioning
confidence: 99%
“…Likewise, the DNA repair protein XRCC3, which is induced by genotoxic stress, can up-regulate DDR1 expression (Martinez-Marignac et al, 2011). The DDR1 gene also contains a hnRNP A2 response element sequence, which may be involved in alternative splicing and nuclear export of DDR1 mRNA in oligodendrocytes (Roig et al, 2012). DDR1 expression is downregulated during induction of epithelial-mesenchymal transition (EMT).…”
Section: Ddr Structure and Ligand Interactionsmentioning
confidence: 99%
“…A2‐mediated RNA transport is specific to an A2RE or A2RE‐like motif, which can be found in a large number of RNAs, such as the mRNA of MBP (Makeyev & Liebhaber, 2002), CaMKII (Ca2+/calmodulin‐dependent protein kinase II, Arc (activity‐regulated cytoskeleton‐associated protein), neurogranin (Gao, Tatavarty, Korza, Levin, & Carson, 2008), MAP2A, GABA receptor α (Munro et al, 1999), and Discoidin domain receptor 1 (Roig, Moyano, Martorell, Costas, & Vilella, 2012). However, the A2 protein also mediates noncanonical motif transport pathways.…”
Section: Hnrnpa2/b1 In Rna Biologymentioning
confidence: 99%
“…Similarly, overexpression of the DNA repair protein XRCC3, results in DDR1 upregulation by an as yet unknown mechanism [73]. A recent study in oligodendrocytes found that the DDR1 gene contains an hnRNP A2 response element-like sequence, which may be involved in alternative splicing and nuclear export of DDR1 mRNA [74]. Also, DDR1 mRNA is a direct target of the microRNA miR-199a-5p; levels of miR-199a-5p inversely correlate with DDR1 expression in human hepatocellular carcinoma cells [75].…”
Section: Regulation Of Ddr Expressionmentioning
confidence: 99%